(untitled) (Modern information system and technologies, 2018)
In this paper, the automatic control system of an incubation system with a wireless monitoring system was designed by itself. When developing the system, an analysis was made of the shortcomings of existing devices on the market and suggested ways of eliminating them when developing this project. The system is designed to facilitate the use of incubation equipment and to increase the reliability of the incubation process. Keywords: incubator, incubation systems, control unit, Wi-Fi, external memory, LCD display.